Longitudinal study of CTX-M ESBL-producing E. coli strains on a UK dairy farm. (December 2016) - Horton, R.A.; Duncan, D.; Randall, L.P.; Chappell, S.; Brunton, L.A.; Warner, R.; Coldham, N.G.; Teale, C.J.
Abstract: The aim of this study was to investigate the bacterial strains and farm environment that may contribute to the persistence of ESBL-producing E. coli on a single UK dairy farm. A longitudinal study was conducted comprising 6 visits, between August and October 2010, followed by a further visit at approximately 69 weeks after the initial visit. Faecal and environmental samples were collected from different parts of the farm. The persistence and extent of faecal shedding of ESBL E. coli by individual calves was also determined. Twenty two different PFGE types were identified. Four of these were persistent during the study period and were associated with serotypes: O98, O55, O141 and O33. The counts suggest that shedding in calf faeces was an important factor for the persistence of strains, and the data will be useful for parameterising mathematical models of the spread and persistence of ESBL strains within a dairy farm. Highlights: Persistence of ESBL producing E. coli strains is associated with cattle faeces. Persistent strains of E. coli were associated with serotypes O98, O55, O141 and O33. Persistence of ESBL E. coli strains may be associated with the use of waste milk. The data should inform models for the spread of ESBL strains within a dairy farm.